"Best Case/Worst Case": Qualitative Evaluation of a Novel Communication Tool for Difficult in‐the‐Moment Surgical Decisions. Issue 9 (17th August 2015) - Kruser, Jacqueline M.; Nabozny, Michael J.; Steffens, Nicole M.; Brasel, Karen J.; Campbell, Toby C.; Gaines, Martha E.; Schwarze, Margaret L.
<x xml:space="preserve">Abstract</x> Objectives To evaluate a communication tool called "Best Case/Worst Case" (BC/WC) based on an established conceptual model of shared decision‐making. Design Focus group study. Setting Older adults (four focus groups) and surgeons (two focus groups) using modified questions from the Decision Aid Acceptability Scale and the Decisional Conflict Scale to evaluate and revise the communication tool. Participants Individuals aged 60 and older recruited from senior centers (n = 37) and surgeons from academic and private practices in Wisconsin (n = 17). Measurements Qualitative content analysis was used to explore themes and concepts that focus group respondents identified. Results Seniors and surgeons praised the tool for the unambiguous illustration of multiple treatment options and the clarity gained from presentation of an array of treatment outcomes. Participants noted that the tool provides an opportunity for in‐the‐moment, preference‐based deliberation about options and a platform for further discussion with other clinicians and loved ones. Older adults worried that the format of the tool was not universally accessible for people with different educational backgrounds, and surgeons had concerns that the tool was vulnerable to physicians' subjective biases. Conclusion The BC/WC tool is a novel decision support intervention that may help facilitate difficult decision‐making for older adults and their physicians when considering invasive, acute medical treatments such as surgery.